Meaning and Challenges: Mothers Experiences in Caring for Children with Mild Intellectual Disabilities - Wianti, Sri; Wijayanti, Wijayanti (Inspirasi Foundation, 2024)
Introduction: Caring for children with mild intellectual disabilities poses significant emotional and social challenges for mothers, often compounded by stigma and limited support. In Indonesia, spirituality and social support play a crucial role in strengthening resilience and framing caregiving as a moral responsibility. Objective: This study aims to explore how mothers perceive the care of children with mild intellectual disabilities and the coping strategies they employ to address physical, emotional, and social challenges. Method: A qualitative phenomenological approach was used, involving semi-structured in-depth interviews with 10 mothers. Data saturation was reached with the eighth participant, confirming no emergence of new significant information. Participants were selected through purposive sampling. Thematic analysis was conducted, complemented by source and theoretical triangulation to enhance the validity of findings. Results: Four key themes emerged from the analysis: (1) caregiving as an act of worship and moral responsibility, where mothers view their role as a life calling; (2) challenges in caregiving, including physical strain, emotional stress, and stigma-related pressures; (3) coping strategies that rely on social and spiritual support, with family and religious communities serving as key resources; and (4) the inadequacy of formal services, which often forces mothers to depend on community and faith-based organizations. Conclusion: This study highlights the need for community-based programs that address the emotional and spiritual needs of families with children with special needs. Effective collaboration between healthcare providers, community organizations, and religious leaders is crucial for developing inclusive and responsive services tailored to the needs of these families.